ÙØ¹Ø§Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø·Ø±ÙŠÙ‚Ø© ØªØ¹Ù„ÙŠÙ… Ù„ØºØ© Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ Ùˆ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… - Diak Islamika Putri; Moh Riadhi (Lughatu Ad-Dhat, 2021)
The background of the research took this method of teaching the language through the community due to the absence of problems in teaching Arabic in the application of methods that can upgrade students' language skills and the absence of teachers of the Arabic language subject to make the method by which listening and speaking can be promoted. Therefore, the research problem is (1) How is the process of teaching the skill of listening and speaking using the method of teaching community language in the Islamic middle school Nahdhat Al-Watan Senior. (2) How effective is teaching the skill of listening and speaking using the method of teaching community language in the Islamic Intermediate School Nahdhat Al-Watan Senior. Then the research approach means quantitative research using data collection tools using interviews, tests and documents. The results showed that there were statistically significant differences between the control group and the experimental group. This difference can be observed from the mean post test score of the control group with a ratio of 70.11, while the experimental group was 75.07. While the t-test of the post-test results of the experimental group resulted in a sig (two-tailed) value of 0.03 <0.05, which means that there is a significant increase in the learning outcomes of students of the experimental group.